"We Don't Need Another One in Our Group": Racism and Interventions to Promote the Mental Health and Well-Being of Racialized International Students in Business Schools. (February 2021) - Wei, ML; Bunjun, Benita
This article is grounded in the premises that racism is a significant predictor of mental health outcomes and that racialized international students experience a great deal of race-based discriminatory treatment. In highlighting how this takes shape in the context of business schools and describing some pedagogical interventions, our purpose is to invite management educators to reflect upon the ways in which they engage with racialized international students and to encourage educators to cultivate approaches that are relevant to their own specific positionalities and institutions. This is especially important as international students comprise a substantial percentage of total enrollment in many business schools and student health and well-being are intimately tied to academic and achievement outcomes. Pedagogical interventions require an understanding of the precarity and exclusion experienced by students while acknowledging the economic and political power structures that are at play as students move around the world to study in countries such as the United States, Canada, and Australia.